A 5 MW direct-drive generator for floating spar-buoy wind turbine: Drive-train dynamics. (February 2017) - Sethuraman, Latha; Xing, Yihan; Venugopal, Vengatesan; Gao, Zhen; Mueller, Markus; Moan, Torgeir
This article proceeds with investigations on a 5 MW direct-drive floating wind turbine system (FWTDD) that was developed in a previous study. A fully integrated land-based direct-drive wind turbine system (WTDD) was created using SIMPACK, a multi-body simulation tool, to model the necessary response variables. The comparison of blade pitch control action and torque behaviour with a similar land-based direct-drive model in HAWC2 (an aero-elastic simulation tool) confirmed that the dynamic feedback effects can be ignored. The main shaft displacements, air-gap eccentricity, forces due to unbalanced magnetic pull (UMP) and the main bearing loads were identified as the main response variables. The investigations then proceed with a two-step de-coupled approach for the detailed drive-train analysis in WTDD and FWTDD systems. The global motion responses and drive-train loads were extracted from HAWC2 and fed to stand-alone direct-drive generator models in SIMPACK. The main response variables of WTDD and FWTDD system were compared. The FWTDD drive-train was observed to endure additional excitations at wave and platform pitch frequencies, thereby increasing the axial components of loads and displacements. If secondary deflections are not considered, the FWTDD system did not result in any exceptional increases to eccentricity and UMP with the generator design tolerances being fairly preserved. The bearing loading behaviour was comparable between both the systems, with the exception of axial loads and tilting moments attributed to additional excitations in the FWTDD system.